The Old Testament encounters Archaeology: the controversy between Sayce and Driver - Davey, Christopher J. (Buried History: The Journal of the Australian Institute of Archaeology, 2024)
The context and content of the debate between Archibald Henry Sayce, Professor of Assyriology and Samuel Rolles Driver, Regius Professor of Hebrew, Oxford University, are described. The inter-related backgrounds of both men are discussed. While Sayce’s criticism was focussed on the literary analysis of the Old Testament, Driver criticised Sayce’s aims, which he had misunderstood. The debate revealed that different methodologies were applied by the two men and these reflected the distinct mindsets associated with archaeological research and biblical studies.